Pemenuhan Asas Persidangan Terbuka Untuk Umum dalam Persidangan Secara Elektronik - Vincentius Patria Setyawan (Program Studi Magister Ilmu Hukum Universitas Kader Bangsa, 2022)
Writing this article will discuss the problems related to the implementation of electronic trials in the answer-and-responsibility agenda (oral-debate) and the agenda for reading decisions that do not realize the principle of an open trial. These problems make it difficult for the public to know the course of criminal case investigations in court. The research and writing of this article aims to understand the holding of electronic trials that are open to the public, and to find out the problems in the form of barriers to public access to obtaining information about court decisions. The writing of this article uses a normative research method, with a conceptual and statutory approach. The legal materials used in writing this article are primary legal materials and secondary legal materials. Keywords: Electronic Trial, Trial Open to the Public, Court Verdict.